THE ROLE OF THE GOVERNMENT OF NORTH ACEH DISTRICT, LHOKSEUMAWE CITY AND BIREUN DISTRICT IN BUMDES MANAGEMENT - Likdanawati; Hamdiah; Sutriani; Rico Nur Ilham; Frengki Putra Ramansyah; Muhammad Multazam (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Currently, the government continues to strive to build and develop the rural economy through community empowerment programs with the aim of increasing productivity, business diversity and regional potential with the aim of improving the economy and welfare of rural communities. One of the government's programs is by providing a budget for funds in the field of community empowerment used to support the capital for the establishment of Village-Owned Enterprises (BUMDes). Where in accordance with the objectives of BUMDes, namely optimizing the management of village assets and existing village potentials, in order to support the village economy, and improve the welfare of rural communities. But unfortunately until now the role and function of BUMDes has not been effective and has not been felt by the community. This is due to the inability and lack of professionalism of BUMDes management human resources and the lack of integration of businesses managed by BUMDes with existing village potentials so that it seems as if BUMDEs stands only as a formality without supporting the economic potential of the village community. The purpose of this study is to create a strategic concept in BUMDes management so that it runs more effectively and on target so that it can support the village economy through the development of human resource knowledge in BUMDes management that is integrated with the economic potential of the village community. So that BUMDes and Basic Pontesial village are integrated into a business institution that actually supports the village economy for the welfare of the village community. This solution can help village communities in strengthening their economy and provide a view of knowledge and open insights to BUMDes managers so that they can develop BUMDes into a business that synergizes with the community.